SUCCESS ANALYSIS OF WEBSITE DINAS PERPUSTAKAAN DAN KEARSIPAN PROVINSI JAWA TIMUR BY DELONE AND MCLEAN MODELS - Sari, Dhya; Sulistiowati, Sulistiowati; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
The vision of the Dinas Perpustakaan dan kearsipan Provinsi Jawa Timur, "East Java fond of Reading and orderly Archives". One of its mission is to manifest the people of East Java fond of reading.  Website is one of the library's facilities and infrastructure that should be improved. Based on flagcounter, total averages visitors during the last three months is around 5,013 visitors (Flagcounter, 2017). After implemented, it has never done evaluation concerning the system quality, information quality, and service quality of the Website. Based on the existing problems, analyzing the success can be used as consideration for owner of the Website in developing the Website. Analysis of success in this research using DeLone and McLean by analyzing the system quality, information quality, service quality, use, user satisfaction, and Net Benefit of the Website. Research results on a sample questionnaire spread with 130 general public, indicating that the variable information quality is positive and significant effect against user satisfactions. User Satisfaction variable is positive and significant effect against Net Benefit. The variable information quality has significantly influencing variable Net Benefit through the intervening of user satisfaction. Recomendation for owner of the website should enhance timeliness, the existence of access, access speed, use of interest, and has a clear objective on websites.